Heat treatment process for improving mechanical properties of aluminum alloy forgings

CN122918472APending Publication Date: 2026-10-16HUBEI TRI RING FORGING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611201085.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该类工艺能够获得一定强度,但在复杂锻件上仍存在若干问题:一是锻造前后温度窗口较宽,局部变形量分配不合理时容易形成粗晶区或低变形死区,使不同位置的力学性能存在差异;二是普通温水淬火依赖水温和搅拌状态,锻件入水瞬间形成的蒸汽膜具有随机性,凸台、凹槽和筋板附近的蒸汽膜破裂时间不同,导致局部换热系数差异明显;三是为了降低淬火畸变而提高水温或降低搅拌强度时,容易牺牲强化元素的过饱和度,而直接采用低温强烈水淬又会增加残余应力;四是175℃保温8h左右的时效周期较长,生产效率较低,且淬火后自然停放时间的波动会影响原子团簇形成,进而使短流程量产中的性能一致性不足

Benefits of technology

[0032]1. This invention integrates homogenization, staged forging, two-stage solution treatment, temperature-sensitive composite medium quenching, and short-time aging as a continuous process for coordinated control. Homogenization reduces as-cast segregation, pre-forging and final forging rationally allocate deformation energy, and two-stage solution treatment balances the risk of re-dissolution of strengthening elements and overheating, resulting in a more consistent microstructure and temperature state entering the quenching stage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a kind of heat treatment process of aluminum alloy forge piece of improving mechanical property, belong to aluminum alloy processing technical field.The process includes homogenization treatment, forging treatment, solid solution treatment, composite medium quenching and short time aging in turn;The forged piece after solid solution is transferred to 40-50 ℃ quenching medium in 15s, the quenching medium contains 0.15-0.40wt% temperature-sensitive composite quenching additive, the additive is prepared by coupling single hydroxyl polyether after carboxylation by succinic anhydride terminal, with amino modified boehmite.The polyether segment occurs reversible dehydration shrinkage at high temperature interface, and boehmite skeleton is stable wetting and nucleate boiling, so that the forged piece each area obtains uniform and sufficient cooling speed;With 530-550 ℃ solid solution and 180-190 ℃ short time aging, the uniformity of supersaturated solid solution and precipitated phase distribution can be improved, and the strength, plasticity and dimensional stability are considered, and the aging period is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aluminum alloy processing technology, specifically, it relates to a heat treatment process for improving the mechanical properties of aluminum alloy forgings. Background Technology

[0002] 6082 aluminum alloy belongs to the Al-Mg-Si series of heat-treatable aluminum alloys. It possesses medium to high strength, good corrosion resistance, weldability, and formability, and is commonly used in automotive chassis connectors, suspension components, robotic arm connectors, rail transit load-bearing components, and other forgings with high requirements for lightweighting and comprehensive mechanical properties. These forgings typically have ribs, bosses, corners, and thickness transition zones. During service, they are subjected to combined loads such as tension, bending, torsion, and impact. Therefore, they not only require high tensile strength and yield strength, but also sufficient plasticity, low residual stress, and good batch stability.

[0003] The strengthening of 6082 aluminum alloy mainly relies on the supersaturated solid solution formed after solution treatment and the fine, dispersed Mg-Si strengthening phase precipitated during artificial aging. Dendritic segregation, coarse eutectic phases, and non-equilibrium second phases remaining inside the ingot can affect subsequent forging flow and solution uniformity. Temperature and deformation distribution during forging can alter the degree of recrystallization, fiber flow line continuity, and dislocation storage state. If the solution temperature is too low, strengthening elements such as Mg and Si will not dissolve sufficiently into the matrix; if the solution temperature is too high or the holding time is too long, local overheating, abnormal grain growth, and surface oxidation are likely to occur. Insufficient cooling rate during quenching can lead to premature precipitation of coarse equilibrium or metastable phases in sensitive temperature zones, reducing the potential for subsequent aging strengthening. Excessive cooling and uneven heat transfer in different areas can create significant temperature differences and residual stresses in the thickness transition zone, causing warping, cracking, or deformation during subsequent machining.

[0004] Existing 6082 aluminum alloy forgings typically employ the T6 process, which involves homogenization, hot forging, solution treatment at approximately 530-550℃, water quenching, and prolonged artificial aging at around 175℃. While this process achieves a certain level of strength, several issues remain for complex forgings: First, the wide temperature window before and after forging can lead to the formation of coarse-grained zones or low-deformation dead zones due to improper distribution of local deformation, resulting in differences in mechanical properties at different locations. Second, ordinary warm water quenching relies on water temperature and stirring conditions; the vapor film formed the moment the forging is immersed in water is random, with different rupture times near bosses, grooves, and ribs, leading to significant differences in local heat transfer coefficients. Third, increasing water temperature or decreasing stirring intensity to reduce quenching distortion can easily sacrifice the supersaturation of strengthening elements, while directly using low-temperature, intense water quenching can increase residual stress. Fourth, the aging cycle of approximately 8 hours at 175℃ is relatively long, resulting in low production efficiency, and fluctuations in the natural resting time after quenching can affect atomic cluster formation, leading to insufficient performance consistency in short-process mass production.

[0005] Polymer quenching media can regulate the cooling process by altering the boiling and wetting states of the workpiece surface. However, conventional polyethers or water-soluble polymers tend to form unevenly thick adsorption films at high-temperature interfaces. At low concentrations, their improvement on vapor film stability is limited, while at high concentrations, they may significantly reduce the cooling rate. Inorganic nanoparticles, although they can increase nucleation points and improve wetting, suffer from insufficient dispersion stability in circulating water, and are prone to settling, agglomeration, or clogging of filtration systems after prolonged use. Therefore, how to improve the strength, plasticity, dimensional stability, and batch consistency of 6082 aluminum alloy forgings without significantly increasing equipment investment through the synergistic design of forging microstructure control, solution treatment, controllable quenching interfaces, and short-term aging remains a technical problem to be solved in this field. Summary of the Invention

[0006] In order to solve the technical problems mentioned in the background art, the purpose of this invention is to provide a heat treatment process for improving the mechanical properties of aluminum alloy forgings.

[0007] The objective of this invention can be achieved through the following technical solutions:

[0008] A heat treatment process for improving the mechanical properties of aluminum alloy forgings includes the following steps:

[0009] Step S1, Homogenization treatment: Hold the 6082 aluminum alloy ingot at 550-580℃ for 8-12 hours to make the Mg, Si and other elements in the as-cast structure diffuse evenly and to make the low melting point non-equilibrium phase dissolve back or transform into a more stable dispersed phase. Then air cool to room temperature to obtain a homogenized billet.

[0010] Preferably, a two-stage homogenization process is adopted, first holding at 555-565℃ for 6-8 hours, and then raising the temperature to 570-578℃ at 20-40℃ / h and holding for 2-4 hours; the first stage reduces the risk of local initial melting when directly entering the high-temperature zone, and the second stage improves the diffusion of elements and the degree of spheroidization and discontinuity of coarse phases.

[0011] Step S2, forging treatment: Heat the homogenized billet to 480-520℃ and hold for 1-3 hours to make the temperature of the billet cross section uniform. Then perform pre-forging and final forging. The total deformation is controlled at 60-75%, and the final forging temperature is 400-440℃. After forging, the forging is water-cooled to below 80℃ to reduce the probability of coarse precipitates forming during the slow cooling process after forging.

[0012] Preferably, the pre-forging temperature is 470-500℃ and the deformation is 25-35%. After pre-forging, the temperature is uniformly heated at 455-480℃ for 20-40 minutes, and then the final forging is carried out with a deformation of 35-45%, and the single reduction rate is not higher than 20%. Pre-forging is used to break the residual structure of the cast state and establish continuous flow lines. Short-time temperature uniformity is beneficial to eliminate the cross-sectional temperature difference caused by pre-forging. The final forging at a lower temperature can retain an appropriate amount of deformation energy and limit grain coarsening.

[0013] Step S3, Solution treatment: The forging is solution treated at 530-550℃, and the temperature is maintained for 1.5-2.0h for every 25mm of the maximum cross-sectional thickness of the forging.

[0014] A two-stage solution treatment process is preferred. First, the forging is held at 530-535℃ for 0.5-1.0h to ensure that the internal and external temperatures of the forging are fully balanced and to promote the gradual re-dissolution of easily soluble phases. Then, the temperature is raised to 540-548℃. The holding time of the second stage is determined by subtracting the holding time of the first stage from the total holding time of the two stages. The total holding time of the two stages is controlled at 1.5-2.0h for every 25mm of the maximum cross-sectional thickness to improve the solid solubility of strengthening elements such as Mg and Si in the aluminum matrix, while avoiding local overheating and abnormal grain growth.

[0015] Step S4, Composite medium quenching: After the solution treatment is completed, the forging is transferred to a quenching medium at 40-50℃ within 15 seconds. The quenching medium circulates at a flow rate of 0.3-0.8 m / s to cool the forging to below 80℃.

[0016] Furthermore, the quenching medium is an aqueous solution containing 0.15-0.40 wt% of a temperature-sensitive composite quenching aid, with a pH preferably between 7.0 and 8.5.

[0017] Step S5, Artificial Aging: After quenching, artificial aging is performed within 2 hours at an aging temperature of 180-190℃ for 2.5-3.5 hours, followed by air cooling to room temperature; short-term aging at around 185℃ utilizes the relatively uniform supersaturated solid solution and vacancy distribution after quenching to promote the rapid nucleation of fine and dispersed strengthening phases, thus shortening the production cycle compared to long-term aging at 175℃.

[0018] The temperature-sensitive composite quenching aid is a polyether-grafted boehmite composite, and its preparation method is as follows:

[0019] Step A1, Preparation of Carboxyl-Terminated Polyether: A monohydroxy polyether (polyoxyethylene-polyoxypropylene block polyether copolymer) with a number-average molecular weight of 3000-5000 and a polyoxyethylene segment mass fraction of 35-45% was selected and mixed with succinic anhydride, 4-dimethylaminopyridine, and anhydrous toluene. The mixture was reacted at 90-100℃ for 5-7 hours under dry nitrogen protection. After the reaction, toluene was removed under reduced pressure, and unreacted small molecules were washed with anhydrous diethyl ether and dried under vacuum to obtain the carboxyl-terminated polyether.

[0020] Furthermore, the preferred ratio of monohydroxy polyether, succinic anhydride, 4-dimethylaminopyridine, and anhydrous toluene is 100g:6-10g:0.3-0.6g:250-400mL. One end of the monohydroxy polyether is capped with an inert group, and the hydroxyl group at the other end forms a half-ester with the succinic anhydride. A carboxyl group is introduced at the end of the polyether without forming a large-scale crosslinking.

[0021] Step A2, Preparation of amino-modified boehmite: Boehmite with a D50 particle size of 30-80 nm was added to an 80-90% (v / v) ethanol aqueous solution. After high-speed shearing and ultrasonic dispersion, 3-aminopropyltriethoxysilane was added. The pH was adjusted to 4.5-5.5 with acetic acid. The reaction was carried out at 55-65℃ for 3-5 h. After the reaction was completed, the mixture was centrifuged, washed with ethanol, and vacuum dried at 60-70℃ to obtain amino-modified boehmite.

[0022] Furthermore, the preferred ratio of boehmite, 3-aminopropyltriethoxysilane, and aqueous ethanol solution is 100g:8-12g:800-1200mL. Triethoxysilane hydrolyzes to form silanol, which then condenses with the hydroxyl groups on the surface of boehmite, thereby introducing exposed amino groups onto the surface of boehmite.

[0023] Step A3, Coupling and grafting: Disperse carboxyl-terminated polyether, amino-modified boehmite, dicyclohexylcarbodiimide and N-hydroxysuccinimide in anhydrous N,N-dimethylformamide, and react at 45-55℃ for 6-10 h under dry nitrogen protection. After the reaction, filter to remove urea byproducts, dilute the filtrate and wash it with an ultrafiltration membrane with a molecular weight cutoff of 10000-30000 Da until there are no obvious small molecule residues in the filtrate. Concentrate and vacuum dry to obtain the temperature-sensitive composite quenching aid.

[0024] Furthermore, the preferred ratio of carboxyl-terminated polyether, amino-modified boehmite, dicyclohexylcarbodiimide, N-hydroxysuccinimide, and anhydrous N,N-dimethylformamide is 100g:8-15g:2-4g:0.5-1.0g:300-500mL. After activation, the carboxyl-terminated groups form amide bonds with the amino groups on the surface of the boehmite, thereby fixing the thermosensitive polyether segments onto the surface of the boehmite in a single-end grafting manner.

[0025] The cloud point of the obtained temperature-sensitive composite quenching aid in a 1% (w / w) aqueous solution is preferably 72-85℃. In use, the aid is first prepared as a mother liquor with 10-20 times its mass of deionized water, and then slowly added to circulating water at 40-50℃. After the initial preparation, the mixture should be circulated for at least 30 minutes to ensure thorough dispersion. During continuous production, the mother liquor can be replenished based on refractive index, solid content, or evaporation loss, and foreign particles larger than 20μm should be filtered periodically.

[0026] The mechanism of action of the temperature-sensitive composite quenching aid is as follows:

[0027] First, boehmite, a hydroxyl-containing aluminum-oxygen framework material, has a high interfacial affinity with the natural alumina film on the surface of 6082 aluminum alloy. Grafted with polyether, the boehmite can quickly reach and briefly adsorb onto the forging surface with water flow. Nano-boehmite provides numerous microscale wetting and bubble nucleation sites, reducing the random retention of continuous vapor films in grooves, stiffener roots, and thickness transition zones.

[0028] Second, the polyoxyethylene-polyoxypropylene block polyether exhibits temperature responsiveness. When the forging first enters the quenching medium, the interfacial water layer temperature is higher than the cloud point of the additive. The polyether segments undergo dehydration and shrinkage, and under the anchoring effect of boehmite, a sparse, continuous, and microchannel transient enrichment layer is formed. This layer does not form a thick insulating film like high-concentration ordinary polymers, but rather suppresses the extreme heat transfer peaks caused by the direct impact of local water flow, and allows the vapor film to transition to nucleation boiling in a more uniform manner.

[0029] Third, as the surface temperature of the forging drops below the cloud point, the polyether segments rehydrate and extend, the transient enriched layer dissociates and re-enters the circulating medium, and the forging surface resumes sufficient convective heat transfer. This forms a dynamic control process of "high-temperature interface homogenization - rapid cooling in the medium-temperature zone - gradual cooling in the low-temperature zone," which, while maintaining the average cooling capacity required for the precipitation-sensitive zone of 450-250℃, reduces the cooling rate difference and thermal stress between different areas of the forging.

[0030] Fourth, the polyether segments are chemically bonded to boehmite, which reduces the sedimentation of inorganic particles in circulating water and the uneven enrichment of polyether on the workpiece surface, thus maintaining relatively stable heat transfer characteristics of the quenching medium during multiple batches of use. Uniform quenching is beneficial for obtaining a supersaturated solid solution with a more consistent composition and vacancy distribution. Combined with short-time aging at around 185℃, it allows fine and dispersed Mg-Si strengthening phases to precipitate more uniformly within the grains, reducing the adverse effects of coarse precipitates near grain boundaries and the absence of precipitate bands, thereby achieving a synergistic improvement in strength, plasticity, dimensional stability, and batch consistency.

[0031] The beneficial effects of this invention are:

[0032] 1. This invention integrates homogenization, staged forging, two-stage solution treatment, temperature-sensitive composite medium quenching, and short-time aging as a continuous process for coordinated control. Homogenization reduces as-cast segregation, pre-forging and final forging rationally allocate deformation energy, and two-stage solution treatment balances the risk of re-dissolution of strengthening elements and overheating, resulting in a more consistent microstructure and temperature state entering the quenching stage.

[0033] 2. The self-prepared polyether-grafted boehmite quenching aid combines the reversible interface regulation capability of thermosensitive polyether with the wetting, nucleation, and interface anchoring effects of boehmite. Compared with ordinary polyether alone, its transient interface layer is thinner and more uniform; compared with the direct addition of inorganic nanoparticles, its dispersion stability is higher, which can reduce the difference in vapor film lifetime in different regions of complex structure forgings.

[0034] 3. This invention can still achieve a relatively uniform and sufficient cooling rate under 40-50℃ warm water conditions, thereby reducing residual stress and warping caused by high-strength water quenching, while avoiding strength loss caused by simply increasing water temperature or polymer concentration. After subsequent heat treatment at around 185℃ for about 3 hours, higher tensile strength and yield strength can be obtained, while maintaining good elongation after fracture.

[0035] 4. Compared with the conventional aging process of holding at 175℃ for about 8 hours, the aging holding time of the present invention is shortened to 2.5-3.5 hours, which can reduce furnace time occupation and energy consumption; the equipment required for the process can be implemented using existing homogenization furnaces, forging equipment, solution furnaces, circulating quenching tanks and aging furnaces, only requiring the addition of auxiliary agent preparation and concentration monitoring, which is easy to promote on existing production lines. Detailed Implementation

[0036] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0037] The 6082 aluminum alloy used in this embodiment has the following composition:

[0038] The composition is as follows: Si: 1.02%, Mg: 0.86%, Mn: 0.62%, Fe: 0.24%, Cu: 0.04%, Cr: 0.08%, Zn: 0.03%, Ti: 0.03%, with other impurities totaling 0.07%, and the balance being Al. The number average molecular weight of the monohydroxy polyether (polyoxyethylene-polyoxypropylene block polyether copolymer) is approximately 4000, and the mass fraction of polyoxyethylene segments is approximately 40%; the boehmite D50 particle size is approximately 50 nm.

[0039] Preparation Example 1: Preparation of Temperature-Sensitive Composite Quenching Aid Q-1

[0040] Step A1: Add 100g of monohydroxy polyoxyethylene-polyoxypropylene block polyether, 8g of succinic anhydride, 0.45g of 4-dimethylaminopyridine, and 320mL of anhydrous toluene to a reactor equipped with a mechanical stirrer, reflux condenser, and nitrogen inlet. Purge with dry nitrogen for 20min and react at 95℃ for 6h. After the reaction is complete, remove toluene under reduced pressure. Wash the residue three times with anhydrous diethyl ether and dry under vacuum at 55℃ for 8h to obtain carboxyl-terminated polyether.

[0041] Step A2: Add 100g of boehmite to 900mL of 85% (v / v) ethanol aqueous solution, shear at 5000rpm for 15min and sonicate for 20min, add 10g of 3-aminopropyltriethoxysilane, adjust the pH to 5.0 with acetic acid, and stir at 60℃ for 4h. After the reaction is complete, centrifuge, wash three times with ethanol, and dry under vacuum at 65℃ to obtain amino-modified boehmite.

[0042] Step A3: Add 100g of carboxyl-terminated polyether, 12g of amino-modified boehmite, 3g of dicyclohexylcarbodiimide, 0.8g of N-hydroxysuccinimide, and 400mL of anhydrous N,N-dimethylformamide to a drying reactor. Purge with nitrogen and react at 50℃ for 8 hours. Filter to remove insoluble byproducts, dilute with an equal volume of deionized water, and wash using an ultrafiltration membrane with a molecular weight cutoff of 20000 Da. After concentration, vacuum dry at 55℃ to obtain temperature-sensitive composite quenching aid Q-1. The cloud point of a 1% aqueous solution of Q-1 is 78℃.

[0043] Preparation Example 2: Preparation of Temperature-Sensitive Composite Quenching Aid Q-2

[0044] Referring to Preparation Example 1, in step A1, the amounts of monohydroxy polyether, succinic anhydride, 4-dimethylaminopyridine, and anhydrous toluene were 100 g, 6 g, 0.3 g, and 250 mL, respectively, and the reaction temperature was 90 °C for 7 h. In step A2, the amount of 3-aminopropyltriethoxysilane was 8 g, and the reaction temperature was 55 °C for 5 h. In step A3, the amounts of amino-modified boehmite, dicyclohexylcarbodiimide, and N-hydroxysuccinimide were 8 g, 2 g, and 0.5 g, respectively, and the reaction temperature was 45 °C for 10 h. The remaining operations were the same, yielding temperature-sensitive composite quenching aid Q-2, with a cloud point of 83 °C for a 1% aqueous solution.

[0045] Preparation Example 3: Preparation of Temperature-Sensitive Composite Quenching Aid Q-3

[0046] Referring to Preparation Example 1, in step A1, the amounts of monohydroxy polyether, succinic anhydride, 4-dimethylaminopyridine, and anhydrous toluene were 100 g, 10 g, 0.6 g, and 400 mL, respectively, and the reaction temperature was 100 °C for 5 h. In step A2, the amount of 3-aminopropyltriethoxysilane was 12 g, and the reaction temperature was 65 °C for 3 h. In step A3, the amounts of amino-modified boehmite, dicyclohexylcarbodiimide, and N-hydroxysuccinimide were 15 g, 4 g, and 1.0 g, respectively, and the reaction temperature was 55 °C for 6 h. The remaining operations were the same, yielding the temperature-sensitive composite quenching aid Q-3, with a cloud point of 74 °C for a 1% aqueous solution.

[0047] Example 1: Preparation of 6082 aluminum alloy forgings

[0048] Step S1: Heat the ingot to 555℃ and hold for 8 hours. Increase the temperature to 570℃ at 30℃ / h and continue holding for 4 hours. Remove from the furnace and air cool to room temperature. Machining removes the surface oxide layer and unloads the ingot.

[0049] Step S2: Heat the billet to 480℃ and hold for 3 hours. Then, pre-forge at 475℃ with a pre-forging deformation of 30%. After that, heat at 460℃ for 40 minutes and then perform final forging with a final forging deformation of 35% and a final forging temperature of 405℃. After forging, cool in water at 30℃ to below 80℃.

[0050] Step S3: Hold the forging at 530℃ for 1 hour, then raise the temperature to 540℃ and hold for 2 hours. After solution treatment, transfer it to a quenching medium at 45℃ within 12 seconds. The quenching medium contains 0.20wt% Q-1 and the circulation flow rate is 0.4m / s. Cool it to 75℃ and then remove it from the quenching medium.

[0051] Step S4: After quenching, start aging and heating for 60 minutes, hold at 182℃ for 3.2 hours, remove from the furnace and air cool to room temperature to obtain the forging of Example 1.

[0052] Example 2: Preparation of 6082 aluminum alloy forgings

[0053] Step S1: Heat the ingot to 560℃ and hold for 7 hours. Increase the temperature to 574℃ at 30℃ / h and continue holding for 3 hours. Remove from the furnace, air cool, and unload.

[0054] Step S2: Heat the billet to 500℃ and hold for 2 hours. Pre-forge at 490℃ with a pre-forging deformation of 32%. After averaging at 470℃ for 30 minutes, perform final forging with a final forging deformation of 40% and a final forging temperature of 420℃. After forging, water cool to below 80℃.

[0055] Step S3: Hold the forging at 532℃ for 0.8h, then raise the temperature to 545℃ and hold for 2h. After solution treatment, transfer it to a quenching medium at 45℃ within 10s. The quenching medium contains 0.28wt% Q-2 and the circulation flow rate is 0.6m / s. Cool it to 70℃ and then remove it from the quenching medium.

[0056] Step S4: After quenching, start aging heating 30 minutes later, hold at 185℃ for 3 hours, and air cool to room temperature to obtain the forging of Example 2.

[0057] Example 3: Preparation of 6082 aluminum alloy forgings

[0058] Step S1: Heat the ingot to 565℃ and hold for 6 hours. Increase the temperature to 578℃ at 25℃ / h and continue holding for 2 hours. Remove from the furnace, air cool, and unload.

[0059] Step S2: Heat the billet to 520℃ and hold for 1 hour. Pre-forge at 500℃ with a pre-forging deformation of 35%. After homogenizing at 480℃ for 20 minutes, perform final forging with a final forging deformation of 40% and a final forging temperature of 435℃. After forging, water cool to below 80℃.

[0060] Step S3: Hold the forging at 535℃ for 0.5h, then raise the temperature to 548℃ and hold for 2.4h. After solution treatment, transfer it to a 50℃ quenching medium containing 0.40wt% Q-3 within 8s, with a circulation rate of 0.8m / s. Cool it to 75℃ and remove it from the quenching tank.

[0061] Step S4: After quenching, start aging heating 15 minutes later, hold at 188℃ for 2.8 hours, and air cool to room temperature to obtain the forging of Example 3.

[0062] Example 4: Preparation of 6082 aluminum alloy forgings

[0063] Step S1: Hold the ingot at 570℃ for 10 hours, then remove it from the furnace, air cool it, and unload it.

[0064] Step S2: Heat the billet to 500℃ and hold for 2 hours, then perform two-stage forging with a total deformation of 70% and a final forging temperature of 425℃. After forging, water cool to below 80℃.

[0065] Step S3: Solution treat the forging at 545℃, and hold for 1.8 hours for every 25mm of maximum cross-sectional thickness. In this example, the holding time is 2.9 hours. After solution treatment, transfer the forging to a 40℃ quenching medium containing 0.15wt% Q-1 with a circulation rate of 0.5m / s within 14 seconds.

[0066] Step S4: After quenching, hold at 185℃ for 3 hours for 45 minutes, then air cool to room temperature to obtain the forging of Example 4.

[0067] Comparative Example 1 uses the conventional T6 process: the ingot is homogenized at 560℃ for 10 hours; the billet is forged after being held at 500℃ for 2 hours, with a total deformation of about 70% and a final forging temperature of about 425℃; the forging is solution-treated at 540℃ for 3 hours, and then transferred to ordinary water at 45℃ for static quenching within 12 seconds; after quenching, it is left to stand naturally for 4 hours and then aged at 175℃ for 8 hours.

[0068] Comparative Example 2, referring to Example 2, did not add the temperature-sensitive composite quenching aid to the 45°C circulating water, and all other aspects were the same as in Example 2.

[0069] Comparative Example 3, referring to Example 2, except that Q-2 was replaced with the same concentration of ungrafted monohydroxy polyether, and all other aspects were the same as in Example 2.

[0070] Comparative Example 4, referring to Example 2, except that Q-2 was replaced with a composition of ungrafted polyether and amino-modified boehmite directly physically mixed in a mass ratio of 100:12, and all other aspects were the same as in Example 2.

[0071] Comparative Example 5, referring to Example 2, increased the concentration of Q-2 in the quenching medium to 0.80 wt%, while the rest were the same as in Example 2.

[0072] The following tests were conducted on the aluminum alloy samples after the above heat treatment:

[0073] Room temperature tensile properties: Proportional tensile test specimens were machined at the same position along the main line direction of each forging. Five specimens were taken from each group and tensile tests were conducted at room temperature. The tensile strength Rm, the specified plastic extension strength Rp0.2, and the elongation after fracture A were recorded, and the average value was taken.

[0074] Brinell hardness: Three test points were selected in the thick area, thin area and transition area of ​​the forging, and the test was performed under HBW 2.5 / 62.5 conditions. The average value of each point was taken.

[0075] Impact absorption energy: Five U-shaped notch specimens were machined at the same position on the forgings, and the impact absorption energy per unit cross-sectional area was tested and calculated at room temperature.

[0076] Warpage: Before and after heat treatment, the forgings are placed on the same reference platform, and the thick area, thin area, stiffener end and two side mounting surfaces are measured using a three-coordinate measuring machine to calculate the maximum deviation relative to the design reference surface.

[0077] Grain size and performance uniformity: Metallographic samples were prepared in thick, thin and thick transition areas, observed under polarized light after anodic coating and the average grain size was calculated by the truncation method; 5 batches were prepared continuously using the same process, and 5 pieces were randomly selected from each batch to test the tensile strength, and the coefficient of variation was calculated based on the average value of each batch.

[0078] The test results are shown in Table 1:

[0079] Table 1

[0080] Group Rm / MPa Rp0.2 / MPa A / % Hardness / HBW Example 1 369 333 12.2 110 Example 2 379 344 12.6 113 Example 3 382 348 11.8 114 Example 4 371 336 12.4 111 Comparative Example 1 341 305 9.1 103 Comparative Example 2 356 321 9.9 107 Comparative Example 3 362 327 10.6 108 Comparative Example 4 365 330 10.8 109 Comparative Example 5 347 313 11.7 104 <![CDATA[Impact absorbed energy / (J·cm -2 )]]> Maximum warpage / mm Average grain size / μm Coefficient of variation / % Example 1 22.8 0.18 34 1.8 Example 2 24.1 0.14 29 1.3 Example 3 23.3 0.15 28 1.5 Example 4 23.0 0.19 33 1.9 Comparative Example 1 17.2 0.34 48 4.2 Comparative Example 2 18.5 0.29 42 3.3 Comparative Example 3 20.1 0.24 39 2.7 Comparative Example 4 20.6 0.22 37 2.5 Comparative Example 5 22.1 0.17 36 2.2

[0081] As shown in Table 1, the tensile strength of Examples 1-4 was 369-382 MPa, and the elongation after fracture was 11.8-12.6%, maintaining good plasticity while improving strength. The maximum warpage was 0.14-0.19 mm, significantly lower than that of Comparative Example 1 (conventional process) and Comparative Example 2 (no additives). The average grain size of the examples was small, and the coefficient of variation of tensile strength in consecutive batches was no higher than 1.9%, indicating a good synergistic relationship between forging, solution treatment, temperature-sensitive composite quenching, and short-time aging.

[0082] Comparative Example 1, which underwent ordinary hydrostatic quenching and long-term aging at 175°C, exhibited lower strength, plasticity, and dimensional stability than the Example, and required a longer aging time. Comparative Example 2, after simply removing the additives, showed a decrease in tensile strength and elongation, and an increase in warpage and batch-to-batch coefficient of variation, indicating that relying solely on 45°C circulating water is insufficient to stabilize the vapor film rupture process on complex surfaces.

[0083] Comparative Example 3, using ungrafted polyether, showed better performance than ordinary water quenching but lower performance than the example, indicating that the temperature-sensitive regulation of polyether can play a certain role. However, without boehmite anchoring and micronucleation structures, the spatial uniformity of the interfacial enrichment layer was insufficient. Comparative Example 4, using a physical mixture of polyether and amino-modified boehmite, showed slightly better performance than polyether alone. However, during cycling, there was gradual sedimentation of inorganic particles and fluctuations in the ratio of polyether to particles reaching the workpiece surface, and it still did not achieve the stable effect of the chemically grafted composite.

[0084] Comparative Example 5 showed good warpage and elongation when the concentration of the additive was increased to 0.80 wt%, but the tensile strength and yield strength decreased significantly. This indicates that excessively high concentrations will result in an excessively thick polyether enrichment layer at the high-temperature interface, which weakens the average cooling capacity in the precipitation-sensitive temperature zone.

[0085] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0086] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A heat treatment process for improving the mechanical properties of aluminum alloy forgings, characterized in that, Includes the following steps: Step S1: Homogenize the 6082 aluminum alloy ingot at 550-580℃ for 8-12 hours, then air cool it to room temperature to obtain a homogenized billet; Step S2: Heat the homogenized billet to 480-520℃ and hold it for 1-3 hours before forging. Control the total deformation to 60-75% and the final forging temperature to 400-440℃. After forging, water cool it to below 80℃ to obtain the forging billet. Step S3: The forging billet is solution treated at 530-550℃, and the temperature is maintained for 1.5-2.0h for every 25mm of the maximum cross-sectional thickness of the forging; Step S4: After the solution treatment is completed, transfer the forging to a quenching medium at 40-50°C within 15 seconds, and circulate and stir to cool it to below 80°C. The quenching medium is an aqueous solution containing 0.15-0.40 wt% of temperature-sensitive composite quenching aid. Step S5: After quenching, heat the forging to 180-190℃ within 2 hours, hold for 2.5-3.5 hours, and then air cool to room temperature; The temperature-sensitive composite quenching aid is prepared by carboxylating a monohydroxy polyether with succinic anhydride, and then coupling the resulting carboxyl-terminated polyether with amino-modified boehmite.

2. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 1, characterized in that, The homogenization process in step S1 includes a first stage and a second stage performed sequentially. The temperature of the first stage is 555-565℃ and the holding time is 6-8h. The temperature of the second stage is 570-578℃ and the holding time is 2-4h. The heating rate from the first stage to the second stage is 20-40℃ / h.

3. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 1, characterized in that, The forging in step S2 includes pre-forging and final forging. The pre-forging temperature is 470-500℃ and the deformation is 25-35%. After pre-forging, the temperature is uniformly heated at 455-480℃ for 20-40 minutes before final forging. The deformation of the final forging is 35-40%. The single reduction rate during the forging process is not higher than 20%.

4. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 1, characterized in that, The solution treatment in step S3 is a two-stage solution treatment: first, it is held at 525-535℃ for 0.5-1.0h, and then the temperature is raised to 540-548℃. The holding time of the second stage is determined by subtracting the holding time of the first stage from the total holding time, and the total holding time of the two stages is controlled to be 1.5-2.0h for every 25mm of the maximum cross-sectional thickness of the forging.

5. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 1, characterized in that, The preparation method of the temperature-sensitive composite quenching aid is as follows: Step A1: Mix monohydroxy polyether, succinic anhydride and 4-dimethylaminopyridine in anhydrous toluene, react at 90-100℃ for 5-7 h under dry nitrogen protection, remove solvent and wash to obtain carboxyl-terminated polyether. Step A2: Disperse boehmite in an aqueous ethanol solution, add 3-aminopropyltriethoxysilane, and react for 3-5 hours at pH 4.5-5.5 and 55-65℃. Separate, wash and dry to obtain amino-modified boehmite. Step A3: Disperse carboxyl-terminated polyether, amino-modified boehmite, dicyclohexylcarbodiimide and N-hydroxysuccinimide in anhydrous N,N-dimethylformamide, react at 45-55℃ for 6-10 h under dry nitrogen protection, filter, purify and dry to obtain the temperature-sensitive composite quenching aid.

6. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 5, characterized in that, The ratio of monohydroxy polyether, succinic anhydride, 4-dimethylaminopyridine and anhydrous toluene is 100g: 6-10g: 0.3-0.6g: 250-400mL.

7. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 5, characterized in that, The ratio of boehmite, 3-aminopropyltriethoxysilane, and aqueous ethanol solution is 100g: 8-12g: 800-1200mL.

8. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 7, characterized in that, The average particle size of boehmite is 30-80 nm.

9. The heat treatment process for improving the mechanical properties of aluminum alloy forgings according to claim 5, characterized in that, The ratio of carboxyl-terminated polyether, amino-modified boehmite, dicyclohexylcarbodiimide, N-hydroxysuccinimide, and anhydrous N,N-dimethylformamide is 100g: 8-15g: 2-4g: 0.5-1.0g: 300-500mL.